Spokane Mountaineering Photo Albums, - Magee, Charles D., 1885-1953
Six photo albums of hiking trips around Washington and Idaho, primarily taken in the 1920s. The albums are well-identified with topographic maps showing the areas where the trips occurred, and then individual photographs are also labeled. Photographs includes mountains, rivers, lakes and other natural areas, as well as pictures of people (sometimes identified), and groups on hiking trips. Some old mining and lumber camps are also included.